Pemberian Pelet FF-999 dengan Dosis Berbeda terhadap Pertumbuhan, Rasio Konversi Pakan dan Kelulushidupan Benih Ikan Nila (Oreochromis Niloticus) pada Sistem Batch - Pratama, Jefri Boy; Julyantoro, Pande Gde Sasmita; Wijayanti, Ni Putu Putri (Current Trends in Aquatic Science; Vol 5 No 1 (2022), 2023)
The purpose of this study was to determine the effect of giving FF-999 pellets with different doses on growth, feed conversion ratio (FCR), survival rate (SR) and water quality of tilapia seeds. This research was conducted at the Fisheries Laboratory, Faculty of Marine Affairs and Fisheries, Udayana University from January-February 2021. Fish samples tested were tilapia seeds ( Oreochromis niloticus ) obtained from UD. Mina Karya Jaya, Karangasem, Bali. Feed used in this study was FF-999 pellets. Method used is an experimental using a completely randomized design with 5 treatments and 3 repetitions. Doses of feed given in this study were in treatment A was 1%, treatment B was 2%, treatment C was 3%, treatment D was 4%, and treatment E was 5%. Results of observations for 8 weeks showed the highest absolute length and weight growth was found in treatment E, was 4.50 cm and 4.34 g. Lowest feed conversion ratio was found in treatment C was 0.81. Highest survival rate was found in treatments C and D, was 73.33%. Results of statistical analysis One-Way ANOVAwith Duncan's follow-up test showed different treatments had significant effect on absolute length and absolute weight growth, survival rate tilapia (P<0.05) and had no significant effect on feed conversion ratio tilapia (P>0, 05). Water quality parameters measured include temperature, pH, Dissolved Oxygen (DO), ammonia, nitrate, nitrite, and phosphate in all treatments was still considered feasible for growth and survival of tilapia seeds ( O. niloticus ).